RETRACTED: Investigating the Co-movement Nexus Between Air Quality, Temperature, and COVID-19 in California: Implications for Public Health - Fareed, Zeeshan; Bashir, Muhammad Farhan; Bilal; Salem, Sultan (Frontiers in Public Health, 2021)
This research aims to look at the link between environmental pollutants and the Covid-19 outbreak in California. To illustrate the COVID-19 outbreak, weather, and environmental pollution, we use daily confirmed cases of COVID-19 patients, average daily temperature, and air quality Index, respectively. To evaluate the data from March 1st to May 24th, 2020, we used continuous wavelet transform and then applied partial wavelet coherence (PWC), wavelet transform coherence (WTC), and multiple wavelet coherence (MWC). Empirical estimates disclose a significant association between these series at different time-frequency spaces. The COVID-19 outbreak in California and average daily temperature show a negative (out phase) coherence. Similarly, the air quality index and COVID-19 also show a negative association circle during the second week of the observed time period. Our findings will serve as policy implications for state and health officials and regulators to combat the COVID-19 outbreak.